Framing Analysis Of Sexual Violence Coverage In Mass Media Rakyat Bengkulu Online In 2021 - Pranciskus, Tupputua; Yanto, Yanto; Asnawati, Asnawati (Universitas Dehasen Bengkulu, 2024)
This research aims to analyze the framing of the news of sexual violence cases in the mass media Rakyat Bengkulu Online in 2021. This research is a qualitative research moving from the empirical field in an effort to build theory from data. The data collection process is carried out by visiting the research site, namely local media in Bengkulu Province by bringing a research format. The results showed that the news framing of sexual violence cases in the mass media Rakyat Bengkulu Online in 2021 where rakyetbengkulu.com tried to report on sexual harassment cases prioritized concern for preventing sexual harassment cases from happening again. In some news, rakyatbengkulu.com does not emphasize how the chronology of events, who are the victims. What is displayed is the number of cases, how it happened so that it still maintains the feelings of the victim, displays words that are only general but easy to understand by readers so as not to cause something that is sensitive to read, and does not harm victims. media becomes a safe space for survivors of sexual violence so that they can speak out without worrying about the confidentiality of their identity.